Comparative morphology of the preimaginal stages of Sesia bembeciformis (Hübner, [1806]) (Lepidoptera: Sesiidae) and other related Sesia species - Bąkowski, Marek (Zootaxa, 2023)
This work presents the first description of the larval morphology of the clearwing moth species Sesia bembeciformis (Hübner, [1806]). The description of the pupa is expanded with new data. All diagnostic morphological features are described in detail, and illustrated with photographs and line drawings. A key to the described larvae of Sesia bembeciformis, S. apiformis, S. yezoensis and S. siningensis is provided. Diagnostic features for the genus Sesia, based on the described larvae and pupae, are proposed and discussed.